THE ROLE OF OPINION LEADERS IN BUILDING PUBLIC PARTICIPATION FOR FOREST CONSERVATION - Bakti , Iriana; Zubair, Feliza; Sjoraida , Diah Fatma (KRIEZ ACADEMY : Journal of development and community service, 2024)
The role of opinion leaders in forest conservation is pivotal in mobilizing public participation and ensuring the sustainability of conservation efforts. Opinion leaders act as crucial intermediaries between communities, governments, and the private sector, facilitating effective coordination and implementation of conservation strategies. This paper synthesizes existing literature to explore how opinion leaders influence public engagement, policy formulation, and the long-term sustainability of forest conservation initiatives. Opinion leaders play multifaceted roles in conservation governance, from advocating for environmental policies that reflect community interests to mobilizing resources and expertise for on-the-ground conservation projects. Their involvement in decision-making processes ensures that civil society voices are heard and integrated into policy-making, fostering inclusive and responsive conservation practices. Moreover, opinion leaders leverage their networks to secure financial support and technical assistance from businesses and non-governmental organizations, thus bolstering the operational capacity of conservation programs. Evaluation of the impact and sustainability of opinion leader-driven conservation efforts reveals significant outcomes beyond physical outputs such as tree planting or protected area expansion. Assessments encompass changes in community attitudes towards, knowledge levels, and behavioral patterns environmental conservation. These evaluations employ diverse methodologies such as surveys, interviews, and direct observations to gauge the broader societal impacts of conservation initiatives led by opinion leaders. Challenges in evaluating these initiatives include data limitations and the complexities of stakeholder relationships, necessitating robust evidence-based approaches to ensure impartiality and comprehensiveness. By identifying supportive factors like effective stakeholder collaboration, local capacity building, and continuous community engagement, evaluations inform strategies to enhance the effectiveness and longevity of conservation efforts. This abstract highlights the critical role of opinion leaders in driving sustainable forest conservation and underscores the importance of comprehensive impact assessments in shaping future conservation policies and practices.